2001
DOI: 10.1161/hh1201.092041
|View full text |Cite
|
Sign up to set email alerts
|

Contraction and Intracellular Ca 2+ Handling in Isolated Skeletal Muscle of Rats With Congestive Heart Failure

Abstract: Abstract-A decreased exercise tolerance is a common symptom in patients with congestive heart failure (CHF). This decrease has been suggested to be partly due to altered skeletal muscle function. Therefore, we have studied contractile function and cytoplasmic free Ca 2ϩ concentration ([Ca 2ϩ ] i , measured with the fluorescent dye indo 1) in isolated muscles from rats in which CHF was induced by ligation of the left coronary artery. The results show no major changes of the contractile function and [Ca 2ϩ ]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
5
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 38 publications
7
73
5
2
Order By: Relevance
“…Studies from our laboratory have demonstrated defective function of RyR1 channels in HF skeletal muscle, which were analogous to those found in RyR2 channels in failing myocardium: PKA hyperphosphorylation of RyR1 and depletion of calstabin-1 (10,27). These findings suggest that defects in RyR1 function could alter intracellular Ca 2ϩ handling and contribute to early fatigue in HF skeletal muscle (40). The present study shows that fixing the defect in RyR1 results in improved performance of HF skeletal muscle, providing important support for the model in which defective regulation of RyR1 plays a role in HF symptoms, including shortness of breath and reduced exercise tolerance.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Studies from our laboratory have demonstrated defective function of RyR1 channels in HF skeletal muscle, which were analogous to those found in RyR2 channels in failing myocardium: PKA hyperphosphorylation of RyR1 and depletion of calstabin-1 (10,27). These findings suggest that defects in RyR1 function could alter intracellular Ca 2ϩ handling and contribute to early fatigue in HF skeletal muscle (40). The present study shows that fixing the defect in RyR1 results in improved performance of HF skeletal muscle, providing important support for the model in which defective regulation of RyR1 plays a role in HF symptoms, including shortness of breath and reduced exercise tolerance.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, observed changes in skeletal muscle cells in HF include a decrease in oxidative enzymes, a shift from slowtwitch to fast-twitch fibers (38), and impaired O 2 utilization (39). In several cases, alterations in SR Ca 2ϩ handling have been documented in skeletal muscle from experimental HF models (40,41). Skeletal muscle Ca 2ϩ transients in animals with HF typically exhibit reduced amplitude and a prolonged relaxation, consistent with altered expression levels of SERCA (41).…”
Section: Discussionmentioning
confidence: 98%
“…This contractile deficit at the whole muscle level has been observed in isolated muscle tissue in animal models (16,21) and in chemically skinned, single muscle fibers in humans (26), suggesting that the heart failure syndrome promotes contractile dysfunction at the level of the myofilaments. In the present study, we investigated the role of individual myofilament components in the decreased skeletal muscle function of heart failure patients.…”
Section: Discussionmentioning
confidence: 85%
“…32 Contrário a esses achados, 33 não encontraram diferenças na expressão de isoformas de SERCA, de receptor para rianodina (RR) e de diferentes subunidades do trocador Na + -Ca 2+ (NCX) utilizando os músculos sóleo e flexor curto dos dedos de ratos controle e ratos com insuficiência cardíaca induzida por ligadura da artéria coronária esquerda. Os resultados controversos do efeito da insuficiência cardíaca na expressão de proteínas envolvidas no transiente de Ca 2+ podem ser explicados por níveis de gravidade e etiologias de insuficiência cardíaca distintos, diferentes espécies estudadas, músculos utilizados distintos e/ou diferentes métodos de análise.…”
Section: Alterações Molecularesunclassified